Glucocorticoids Increase In Vitro and In Vivo Activities of Antibiotics against Chlamydophila pneumoniae - Caronzolo, Dario (American Society for Microbiology, 2004)
The in vitro and in vivo antichlamydial activities of dexamethasone and beclomethasone alone and in combination with an antibiotic were tested. In vitro, dexamethasone and beclomethasone decreased the number of inclusion-forming units versus the control number (P < 0.001). The combination of glucocorticoids with azithromycin, telithromycin, or levofloxacin was more active than antibiotics used alone (P < 0.001). The combination, tested in a murine Chlamydophila pneumoniae infection model, produced similar results.